Experiencia urbana e imágenes colectivas de la Ciudad de México - de Alba, Martha (El Colegio de México A.C., 2006)
This article studies the urban imagination in Mexico City, using the comparison of the perspective of a sample of residents from the Federal District with another sample of functionaries in charge of managing the metropolis. It begins with the assumption that the images this great city evokes correspond to two different registers: on the one hand, the urban experience recorded through the discourse on the city and on the other, the cartographic images materialized in cognitive maps of space. This article presents the results of these two complementary methods of analyzing the representations of the city and proposes a methodology for studying them. It also analyzes whether the experience and the representation of the city correspond to the theoretical proposals suggesting that the contemporary metropolis is no longer a place of coexistence, sociability and identity but has become a purely functional space.